Development of surface functionalization strategies for 3D‐printed polystyrene constructs. Issue 8 (1st March 2019) - Lerman, Max J.; Muramoto, Shin; Arumugasaamy, Navein; Van Order, Michael; Lembong, Josephine; Gerald, Anushka G.; Gillen, Greg; Fisher, John P.
Abstract: There is a growing interest in 3D printing to fabricate culture substrates; however, the surface properties of the scaffold remain pertinent to elicit targeted and expected cell responses. Traditional 2D polystyrene (PS) culture systems typically require surface functionalization (oxidation) to facilitate and encourage cell adhesion. Determining the surface properties which enhance protein adhesion from media and cellular extracellular matrix (ECM) production remains the first step to translating 2D PS systems to a 3D culture surface. Here we show that the presence of carbonyl groups to PS surfaces correlated well with successful adhesion of ECM proteins and sustaining ECM production of deposited human mesenchymal stem cells, if the surface has a water contact angle between 50° and 55°. Translation of these findings to custom‐fabricated 3D PS scaffolds reveals carbonyl groups continued to enhance spreading and growth in 3D culture. Cumulatively, these data present a method for 3D printing PS and the design considerations required for understanding cell–material interactions. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B:2566–2578, 2019.